Impact of visceral fat on gene expression profile in peripheral blood cells in obese Japanese subjects. Issue 1 (December 2016) - Obata, Yoshinari; Maeda, Norikazu; Yamada, Yuya; Yamamoto, Koji; Nakamura, Seiji; Yamaoka, Masaya; Tanaka, Yoshimitsu; Masuda, Shigeki; Nagao, Hirofumi; Fukuda, Shiro; Fujishima, Yuya; Kita, Shunbun; et al.
Abstract Background Visceral fat plays a central role in the development of metabolic syndrome and atherosclerotic cardiovascular diseases. The association of visceral fat accumulation with cardio-metabolic diseases has been reported, but the impact of visceral fat on the gene expression profile in peripheral blood cells remains to be determined. The aim of this study was to determine the effects of visceral fat area (VFA) and subcutaneous fat area (SFA) on the gene expression profile in peripheral blood cells of obese subjects. Methods All 17 enrolled subjects were hospitalized to receive diet therapy for obesity (defined as body mass index, BMI, greater than 25 kg/m2 ). VFA and SFA were measured at the umbilical level by computed tomography (CT). Blood samples were subjected to gene expression profile analysis by using SurePrint G3 Human GE Microarray 8 × 60 k ver. 2.0. The correlation between various clinical parameters, including VFA and SFA, and peripheral blood gene expression levels was analyzed. Results Among the 17 subjects, 12 had normal glucose tolerance or borderline diabetes, and 5 were diagnosed with type 2 diabetes without medications [glycated hemoglobin (HbA1c); 6.3 ± 1.3%]. The mean BMI, VFA, and SFA were 30.0 ± 5.5 kg/m2, 177 ± 67 and 245 ± 131 cm2, respectively. Interestingly, VFA altered the expression of 1354 genes, including up-regulation of 307 and down-regulation of 1047, under the statistical environment that the parametric false discovery rate (FDR) was less than 0.1. However, no significant effects were noted for SFA or BMI. Gene ontology analysis showed higher prevalence of VFA-associated genes than that of SFA-associated genes, among the genes associated with inflammation, oxidative stress, immune response, lipid metabolism, and glucose metabolism. Conclusions Accumulation of visceral fat, but not subcutaneous fat, has a significant impact on the gene expression profile in peripheral blood cells in obese Japanese subjects.